2013
DOI: 10.1002/anie.201303500
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free HB(C6F5)2‐Catalyzed Hydrogenation of Unfunctionalized Olefins and Mechanism Study of Borane‐Mediated σ‐Bond Metathesis

Abstract: Out with the metal: Metal-free hydrogenation of unfunctionalized olefins can be achieved by employing HB(C6F5)2 as the catalyst. The key step in the catalytic reaction is believed to involve a novel borane-mediated σ-bond metathesis, which has been investigated both experimentally and theoretically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 63 publications
2
42
0
5
Order By: Relevance
“…DFT calculations revealed a slightly unsymmetric transition state (Scheme 16). [50] Attempts to effect the reductions of ketones showed that these combinations were too reactive, thus precluding catalytic hydrogenations.…”
Section: Ph]mentioning
confidence: 99%
“…DFT calculations revealed a slightly unsymmetric transition state (Scheme 16). [50] Attempts to effect the reductions of ketones showed that these combinations were too reactive, thus precluding catalytic hydrogenations.…”
Section: Ph]mentioning
confidence: 99%
“…While the homogeneous hydrogenation of alkenes by transition-metal complexes [10] is well-established, "frustrated" Lewis pair (FLP) [11] and main-group-metal [12] hydrogenation catalysts are limited to activated (conjugated) C=Cd ouble bonds.Arare example is the hydrogenation of alkenes using HB(C 6 F 5 ) 2 . [13] Herein we report the synthesis and structural characterization of [Ca 2 H 2 (Me 4 TACD) 2 ] 2+ as the dimer of the hypothetical [CaH] + cation [14] along with its catalytic activity in 1-alkene hydrogenation and isotope exchange reactions.…”
mentioning
confidence: 99%
“…Dieses Anion schien an den Reaktionen mit H 2 und aktivierten Alkenen beteiligt zu sein. [13] Hier berichten wir über die Synthese und Charakterisierung von [Ca 2 H 2 (Me 4 TACD) 2 ] 2+ , das als Dimer des hypothetischen [CaH] + -Kations [14] angesehen werden kann und aktiv in der Hydrierung von 1-Alkenen und dem Isotopenaustausch von H 2 und D 2 ist. Ein seltenes Beispiel fürd ie Hydrierung von Alkenen stellt HB(C 6 F 5 ) 2 dar.…”
unclassified
“…Eine sofortige Verfärbung der Reaktionslçsungen deutete auf die Bildung der entsprechenden Insertionsprodukte hin. [9, 12a] 13,25] Wiei na nderen Fällen [8,19] scheint die positive Ladung entscheidend zu sein, um die Elektrophilie des elektropositiven Calciumzentrums zu steigern und die Hydrierung von nichtaktivierten olefinischen Bindungen zu ermçglichen.…”
unclassified